The Mediating Role of Mental Well-Being Between Psychological Resilience, Life Satisfaction and Emotional Intelligence - Yusuf Akyıl; Yakup İme (e-Kafkas Eğitim Araştırmaları Dergisi, 2024)
Mental well-being holds significance throughout all phases of life, spanning from early years and adolescence to adulthood. The purpose of this research was to investigate the potential mediating effect of mental well-being on the relationship between emotional intelligence, life satisfaction, and psychological resilience, which are all dependent variables. The research involved 317 university students who volunteered, with a majority of 303 being female and 14 male. Results revealed that mental well-being acts as a complete mediator in the link between emotional intelligence and life satisfaction, while it partially mediates the connection between emotional intelligence and psychological resilience. The model suggests that individuals, regardless of their level of emotional intelligence, experience greater life satisfaction and psychological resilience when mental well-being is high. It's expected that those with enhanced psychological resilience and life satisfaction, particularly those with a certain level of emotional intelligence, will see a positive impact on their life trajectory when their mental health is supported and strengthened.